Stock market participation puzzle: a systematic review and bibliometric analysis - Noah Keya Otinga; Pat Obi; Freshia Mugo-Waweru (Cogent Business & Management, 2024)
This paper conducts a systematic review and bibliometric analysis of the literature on the stock market participation puzzle. Addressing the lack of comprehensive summaries in existing literature, this review combines quantitative and qualitative approaches to present detailed insights into the topic. The study examines 199 articles published in peer-reviewed journals from 2000 to 2023. Using citation network analysis, co-citation analysis, content analysis, publication trends, and keyword analysis, we identify influential works, outline the intellectual structure of the field, and highlight research gaps. The analysis reveals several key findings. First, it reveals a notable increase in studies devoted to the stock market participation puzzle. Secondly, the review underscores the variability in SMP measurement across studies, a phenomenon attributable to the diverse and multifaceted nature of research within this domain. Finally, the paper underscores the multifaceted nature of factors influencing stock market participation, emphasizing the intricate challenge of comprehending the non-participation puzzle. Notably, a prominent gap in the literature is the absence of a universally accepted theoretical framework to account for the non-participation behavior. The paper recommends that researchers employ a multi-factor approach to elucidate the complexities of SMP. Importantly, it suggests that this review can provide valuable insights not only for researchers but also for regulators and policymakers, aiding their efforts to understand and address the challenges associated with stock market participation.Limited stock market participation (SMP) remains a key policy concern for both emerging and developed economies, drawing significant attention in academic and scholarly circles. Despite this attention, there is divided opinion on the preconditions for SMP and how policymakers should approach this challenge. This study adopts a systematic review approach complemented by a bibliometric analysis, analyzing 199 finance articles published between 2000 and 2023, to provide insights into the meaning, measurements, and antecedents of SMP. The findings indicate a variability in both the measurement and antecedents of SMP. This variability emphasizes the nuanced nature of the issue, requiring careful consideration and context-specific strategies for effective policy interventions. The study's implications extend beyond the academic realm, offering valuable insights for regulators and policymakers. These findings can aid in their efforts to understand and address the challenges associated with limited stock market participation
Keywords: 650; Stock market participation; systematic literature review; bibliometric analysis; meaning and measurement; participation puzzle